Description of a specialized outpatient clinic as a reference center for children and adolescents living with HIV/AIDS in southern Brazil - da Rocha Carvalho, Emanuela; Tahan, Tony Tannous; Rossoni, Andrea Maciel de Oliveira; Rodrigues, Cristina de Oliveira (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Children living with HIV/AIDS require specialized care. Objective: To describe clinical and epidemiological characteristics of patients living with HIV/AIDS. Methods: Observational, descriptive study using medical records data of patients with HIV/AIDS under 14 years of age. Approved by the institution’s Ethics Committee under number 1,432,517. Results: 60 cases were included; the median follow-up duration was 6.8 years; 50.0% were male; 88.3% were white; 75.0% were from the capital and metropolitan region. Prenatal records were available for 51 cases, but only 44.6% received antiretroviral therapy (ART) during pregnancy (mean duration of 3.3 months). HIV diagnosis was based on clinical symptoms in 28.3% of the cases, occurring in similar proportions for both childhood common infections and opportunistic infections. According to the CDC clinical classification (1994), at the start of follow-up, 56.6% of patients had moderate or severe symptoms, which would be reduced to only 18.3% upon reclassification at the last visit (p=0.016). Initially, 41.7% showed evidence of immunosuppression, compared to 19.9% at the time of the study (p=0.5). Only 6.6% remained asymptomatic. A decrease in the average number of hospitalizations was observed during follow-up. Conclusion: Among the cases diagnosed based on clinical symptoms, half were attributed to common childhood infections and lacked immunosuppression.